A Project feasibility study on Papaya Latex Binder - Chico, Paul; Parco, Mark; Vasquez, Ricky; Yaniza, Gary (College of Engineering, 1989)
A study conducted by a group of high school students from San Beda with the close supervision of the National Science Development Board (NSDB) proved that latex binders used for paints could be obtained from unripe papaya. Our group conducted a study to find out if it is feasible yo extract and refine latex from papaya on a commercial basis. A marketing analysis was therefore conducted. Since the proposed product would be sold to paint companies, it was decided to compile historical data of latex binder consumption by paint companies. However, because of stiff competition in the industry, the paint companies and the latex binder producers refused to give the necessary information. But using the information available, total paint companies and some other factors, the group was able to come up with the projected demand for low cost latex binders. Using geometric growth rate method of analysis it was seen that the demand for the latex binders increases at a rate of 0.78 percent per year. The company was envisioned to capture at least five percent of the market or 54,000 liters of latex emulsion binder annually. The company was not expected to have trouble selling the product. The market being pursued was the latex emulsion binder's market for low cost paints. In this market the quality of the binder could hold the important factor, for as long as the binder could hold the pigment for two to three months it would generally be acceptable to the buying public and the paint producers. The important factor was the price of the binder. The company would have no problem selling the papaya latex binder to paint companies as long as its price was less than the prices of the synthetic latices. As of present there are two synthetic latex binders in the market., Acrylic which sells for P60/kg and Polyvinyl Alcohol (PVA) which sell for P55/kg.